ANGPTL4 regulates the metastatic potential of oral squamous cell carcinoma. (24th July 2014) - Tanaka, Junichi; Irié, Tarou; Yamamoto, Gou; Yasuhara, Rika; Isobe, Tomohide; Hokazono, Chie; Tachikawa, Tetsuhiko; Kohno, Yohko; Mishima, Kenji
<x xml:space="preserve">Abstract</x> Lymph node metastasis is a major factor for poor prognosis in oral squamous cell carcinoma (OSCC). However, the molecular mechanisms of lymph node metastasis are unclear. We determined that angiopoietin‐like protein 4 (ANGPTL4) mRNA and protein expression were increased in OSCC cells established from the primary site in metastatic cases. In addition, ANGPTL4 expression in biopsy specimens was correlated with the presence of lymph node metastasis. Therefore, our initial findings suggest that OSCC cells expressing ANGPTL4 may possess metastatic ability. Furthermore, cell culture supernatants from OSCC cells that metastasized to the lymph node contain ANGPTL4 and promote invasive ability. These findings suggest that secreted ANGPTL4 may affect the invasive ability of OSCC. Moreover, the rates of positive ANGPTL4 expression at the primary site were significantly higher in the lymph node metastasis group. These results demonstrate that ANGPTL4 contributes to OSCC metastasis by stimulating cell invasion. Therefore, ANGPTL4 is a potential therapeutic target for preventing cancer metastasis.